PERGANTIAN PENGURUS PERSEROAN KOMANDITER (CV) KARENA MEWARISI DIKAITKAN DENGAN PERBUATAN HUKUM PERSEROAN KOMANDITER (CV) - AGUSTIAN AGUSTIAN (PREMISE LAW JURNAL, 2017)
In establishing a CV (Limited Partnership), there are 2 types of partners: limited partner and active partner. Active partner acts as a managing partner in a CV. In its development, a problem arises as when the director dies so that the CV has to stop temporarily, including in its legal act toward the third party and vice versa. The result of the research showed that the position of the clause in the changing of active partners can be changed because of saisine principle concerning the right and obligation of the testator’s assets or financial liabilities adhered to his heirs. It is recommended that the regulation of CV should be confirmed, especially about the position and the liability of the new active partner of the CV. Keywords: CV (Limited Partnership), Active Partner, Changing Active Partner because of Inheritance